Severity of residual stenosis of infarct‐related lesion and left ventricular function after single‐vessel anterior wall myocardial infarction: Implication of st‐segment elevation in lead avl of the admission electrocardiograms - Yoshino, Hideaki (Clin Cardiol, 2009)
Background: The relationship between the severity of chronic‐phase stenosis of infarct‐related lesions (IRLs) and chronic left ventricular function in anterior acute myocardial infarctions (AMI) has not been adequately investigated. Hypothesis: This study investigated whether ST elevation in lead aVL of admission electrocardiogram (ECG) would be a determinant factor of the relationship between the severity of stenosis of the IRL and chronic left ventricular function after anterior wall AMI. Methods: One month after AMI, the IRL was evaluated by coronary angiography in 98 patients with anterior AMI, and left ventricular ejection fraction (LVEF) was determined using multigated radionuclide angiocardiography. Patients were classified according to the severity of the IRL: patients with 100% occlusion (Group O), patients with 90 to 99% stenosis (Group H), and patients with ≤ 75% stenosis (Group L). Patients with ST elevation ≥ 0.1 mV in the aVL lead on their admission ECG were included in the ST‐elevation group, and those with ST elevation < 0.1 mV were included in the non‐ST‐elevation group. Results: The LVEF was greater in the non‐ST‐elevation group than in the ST‐elevation group (p<0.0001), and the LVEF in a whole group as follows: Group L LVEF>Group H LVEF>Group O LVEF (p = 0.0160). In the ST‐elevation group, LVEF was higher in Group L than in the other groups (p = 0.0251). There were three independent predictors of a reduced LVEF: ST‐elevation in aVL [odds ratio (OR): 3.38, p = 0.0044], IRL stenosis ≥ 90% (OR: 2.90, p = 0.0044), and the IRL occurring in the left anterior descending artery proximal to the first diagonal branch (OR: 6.31, p = 0.0024). Conclusion: Left ventricular function was preserved, regardless of the severity of residual stenosis, in patients without ST elevation in aVL if the IRL was not totally occluded. In patients with ST elevation in aVL, LVEF was lower in patients with more severe stenosis, even if the IRL was patent.